Funkcjonowanie ubezpieczeń obowiązkowych i dobrowolnych w rolnictwie w świetle projektu dofinansowania ubezpieczeń rolnych w Polsce - Obstawski, Zdzisław (Functioning of Obligatory and Voluntary Insurance in Agriculture in the Context of the State Subsidising Project of Agricultural Insurance in Poland, 2006)
The solution concerning the insurance in agriculture has not so far fully considered the specificity of its operating, and social and economic problems of people living and working in rural areas.The Ministry of Agriculture have prepared a bill stipulating that since 2006 the department will subsidise voluntary natural perils crop insurance and stock insurance.The comparison of conditions stipulated in the Act on Subsidies to crop and stock insurance with general conditions of insurance for farmers offered so far by insurance companies shows that the requirements concerning risk assessment, excess the protection cost were introduced at a very low level. At the same time, the bill stipulates a broad, not existing on the market, scope of insurance protection, including a drought risk. Taking into consideration problems connected with the present system of the agricultural sector insurance system, it may be stated that the new solutions significantly complement the agricultural insurance system and will positively influence the development of insurance in rural areas.At the same time, the author thinks that the process of European integration predestines the EU countries to take up this task and create the outline of common insurance programme supported from the EU budget. The EU programme, by the organization of the system, could ensure the life stabilization of people working in agriculture and food production in all EU countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 172-178